PENGARUH PRAKTEK BERBAGI PENGETAHUAN ORGANISASI TERHADAP KEPUASAN KERJA DENGAN KOMITMEN BELAJAR KARYAWAN DAN ADAPTASI KARYAWAN SEBAGAI VARIABLE MEDIASI PADA PT PUPUK ISKANDAR MUDA ACEH UTARA - Muhammad Rizal Fahluvi, Amri (Departemen Manajemen, 2016)
This study was conduted to examine the effect of Organizational Knowledge Sharing practices against job satisfaction with Employees learning commitment and employees adaptability as a mediating variable study on PT Pupuk Iskandar Muda North Aceh. Respondents in the study were 140 employees of PT Pupuk Iskandar Muda Aceh Utara (Simple random sampling). The analysis model used in this study is path analysis Mediating (Baron Kenny, 1986). Based on result found that organizational knowledge sharing practices is influence positively over job satisfaction, organizational knowledge sharing practices is influence positively over Employees learning commitment, organizational knowledge sharing practices is influence positively over employees adaptability, Employees learning commitment is influence positively over Job satisfaction, employees adaptability is influence positively over Job satisfaction, employees learning commitment and employees adaptability is mediating the relationship between organizational knowledge sharing practices over job satisfaction. Keywords : Organizational Knowledge Sharing Practices, Employees Learning Commitment, Employees Adaptability, Job Satisfaction